Demystifying Powers and Ideologies via Illocutions in Pope Francis’ Pandemic Homilies: A Discourse Analysis - Henry E. Lemana II (CV. Literasi Indonesia, 2023)
The Roman Catholic Church, just like other churches in the world, has seen an unprecedented influx of afflicted followers as fear of death looms around the globe with the spread of an unseeable enemy the Covid-19 pandemic. This study analyzed how the Church's supreme pontiff, Pope Francis, mirrors his intentions in his ten randomly selected homilies to project his powers and ideologies amid the pandemic. Grounded on the supposition of discourse that language reflects and shapes social order and individuals interact and react to the words of others to better themselves and the world, this study revealed that Pope Francis' intentions in delivering the pandemic homilies encompass asserting the theological teachings of the Church, directing the congregation to act, committing himself and his audience to respond as a community, and expressing a mixture of personal emotions, which were revealed through the scrutiny of illocutionary forces used to assert legitimate, expert, and referent powers and profess magisterial, covenantal, volitional, and revelational ideologies. Notably, it could be observed in the findings that there appears to be a unification of powers to mirror the overriding ideologies that emerge. Indeed, the findings imply that the pope's homilies serve multiple purposes, including asserting theological teachings, directing the congregation to act, fostering community response, and expressing personal emotions through illocutionary forces establishing a meaningful correspondence between preaching and communication.